KONSEP KOTA PINTAR DALAM PENERAPAN SISTEM PEMBAYARAN MENGGUNAKAN KODE QR PADA PEMESANAN TIKET ELEKTRONIK - Arman Syah Putra (Fakultas Teknik Universitas Persada Indonesia YAI, 2020)
The background of this research is the problem of developing payment systems that are carried out in almost all fields and in the future almost all payments are no longer using cash, but by using electronic money, with this development the authors use research on electronic money payments in the field of ticket reservations, the method used in this study is to use a proposed system by looking at the current system, and developing the existing system to be a better system, the existing system using a manual ordering system and the payment is still using cash, by using payment with the QR code, it is expected that the ticket booking system will facilitate the public, and not complicate with ordering and payment of tickets, it is expected that the QR code system will be used in ordering bus tickets and plane tickets in the future, and merging the system with s another system will make it better. Keywords: Smart City, E-Ticket, Transportation, System